Study on the Concentration-Dependent Toxic Effects of Ailanthus altissima and Dysphania ambrosioides Extracts on Red Imported Fire Ants - Gu, Rui; Yang, Zhenhong; Tao, Chuan (International Journal of Public Health and Medical Research, 2025)
This study utilized the water test-tube feeding method to assess the toxic effects and behavioral impacts of extracts from Ailanthus altissima and Dysphania ambrosioides at different concentrations (0%, 3%, 6%, 9%) on Solenopsis invicta (red imported fire ants). Single-factor analysis of variance (ANOVA) was employed to statistically analyze behavioral indices such as mortality rate, aggregation rate, pole-climbing rate, attachment rate, and walking rate. The results showed that both the toxicity and behavioral inhibitory effects of the two extracts increased with increasing concentrations, exhibiting a significant concentration-dependent pattern. Notably, the lethality rate of the A. altissima extract reached 96.67% at 9% concentration, while that of D. ambrosioides was 83.33%. These findings support the potential feasibility of using these extracts as biological control agents against S. invicta and provide experimental evidence for the development of plant-derived insecticides.